Prototype of human footstep power generator using ultrasonic sensor - Giva Andriana Mutiara; Andri Surya Dinata; Anang Sularsa (Universitas Ahmad Dahlan, 2019)
Nowadays, the human need for electrical energy is getting higher. Due to the declining supply fuel, many efforts have been studied to find renewable energy. One of the studies is building a power generator system that comes from daily human activities. This paper proposes a human footstep power generator using ultrasonic sensor HC-SR04. Only by doing a simply walking on the ground floor, electrical energy can trigger. An HC-SR04 sensor measuring the spring distances from the footstep and activates the motor drive relay and generator that converts mechanical energy into electrical energy and stored in a battery. The test results state that the deeper of a footing step on the floor surface, the greater distance produced and the higher voltage can be generated. The footstep can trigger 7.5 V-8.8 V. Full battery condition can be used to turn on two pieces of 2-watt LED lamps for approximately 5 hours.